Tamarixinin A Alleviates Joint Destruction of Rheumatoid Arthritis by Blockade of MAPK and NF-κB Activation - Zhuang, Yuanyuan; Liu, Jiabao; Ma, Pei; Bai, Jinye; Ding, Yasi; Yang, Hui; Fan, Yannan; Lin, Mingbao; Li, Shuai; Hou, Qi (Frontiers in Pharmacology, 2017)
Background Tamarixinin A, a natural tannin isolated from Myricaria bracteata, has been confirmed to have moderate anti-inflammatory effects in vitro and in vivo. However, how it effects rheumatoid arthritis (RA) is still unknown. Therefore, the aim of this study is to investigate the therapeutic effects of tamarixinin A on experimental RA, and explore the underlying mechanism. Methods The anti-arthritic effects of tamarixinin A were evaluated on collagen-induced arthritis (CIA) mice and adjuvant-induced arthritis (AIA) rats. The hind paw thickness, inflammatory cytokine levels in serum, and histopathological assessments were determined. The arthritis score was evaluated. Activation of p38 and p65 in AIA rats was also determined. The anti-inflammatory effect in vitro was also tested in LPS induced macrophages, and its related anti-inflammatory signaling pathways were explored. Results Treatment with tamarixinin A significantly suppressed the progression and development of RA in CIA mice and AIA rats. Both in CIA mice and AIA rats, arthritis scores decreased, paw swelling and thickness were reduced, and joint destruction was alleviated. In AIA rats, tamarixinin A significantly inhibited the expression of p38, p-p38 and p65. In addition, tamarixinin A inhibited the production of pro-inflammatory mediators, the phosphorylation of p38, ERK, JNK and p65, as well as the nuclear translocation of p38 in LPS- induced macrophages. Conclusions Tamarixinin A is a potential effective candidate compound for human RA treatment, which executes anti-arthritic effects potentially through down-regulating MAPK and NF-κB signal pathway activation.